EUGLYCEMIC DIABETIC KETOACIDOSIS PRECIPITATED BY HYPERTRIGLYCERIDEMIAINDUCED PANCREATITIS, LIVER ABSCESS AND SODIUM-GLUCOSE COTRANSPORTER-2 INHIBITOR USE IN A PATIENT WITH FAMILIAL HYPERTRIGLYCERIDEMIA - Beh, Yuan Ye; Gnanakkan, Beulah Devakirubai; Selvaraj, Mellvina Arrputham; Sabir, Haslina; Tee, Hwee Ching (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Euglycemic diabetic ketoacidosis (EDKA) has a worse outcome than typical DKA as it is relatively rare and remains a diagnostic challenge. Conditions such as sepsis, pancreatitis, use of sodium-glucose cotransporter-2 inhibitors (SGLT-2i), pregnancy and starvation are known to be associated with EDKA. We report a case of a patient with Type 2 Diabetes Mellitus (T2DM) and familial hypertriglyceridemia on SGLT-2i who presented with hypertriglyceridemia-induced pancreatitis (HTGP) concurrently with EDKA. CASE A 31-year-old female presented with epigastric pain, vomiting and lethargy. The clinical exam revealed tender epigastrium with no guarding and negative Murphy’s. Serum amylase was 242 U/L (Imrie score 2, BISAP 1) and C-reactive protein (446 mg/L). The ultrasound of the abdomen revealed an ill-defined collection (2.3 x 3.2 cm) at segment V of the liver with findings suggestive of chronic pancreatitis. She had three prior admissions due to acute pancreatitis and once complicated by an infected pancreatic pseudocyst. She was diagnosed with T2DM and familial hypertriglyceridemia five years ago, with poorly controlled glucose and lipid profile (HbA1c 8.4%, triglycerides 33.4 mmol/L). She is on an SGLT2 inhibitor, amongst other medications, which she continued taking despite her illness. She developed EDKA in the ward (pH 7.43, PCO2 20, HCO3 14, serum ketone 3.6, lactate 0.8). She was started on DKA treatment, then continued with variable rate insulin sliding scale, fasting, statin, fibrates and intravenous antibiotics. Dietary and lifestyle advice were reinforced. She was discharged well after two weeks (triglyceride 4.2 mmol/L, C-reactive protein 2 mg/L) with resolved symptoms and liver lesions. CONCLUSION EDKA should be a well-recognised diagnosis in an era where there is growing use of SGLT2i, especially in patients with multiple precipitating factors. Physicians must have a high clinical suspicion in patients who are on SGLT-2i in acute illness. In addition, we need to consider that EDKA can precipitate HTGP and vice versa. In both conditions, early initiation of continuous intravenous insulin infusion can improve outcomes.